Hire an American! Economic Tyranny and Corruption in Iraq - Whyte, Dave (Social justice, 2007)
Part of a special section on social justice beyond transnational crime. A study was conducted to examine economic tyranny and corruption in Iraq. Data were obtained from UN, and World Bank documents and from a review of the relevant literature. Findings revealed that, rather than representing a new beginning for Iraq, the post-invasion economic “reconstruction” brought about a corrupt Iraqi economy that is part of the same continuum of economic discipline that started with the UN sanctions regime. Findings indicated that although the sanctions regime began the process of weakening economic autonomy and self-sufficiency, the post-invasion economic upheaval ensured its assimilation into a neoliberal economic order. Findings suggested how the rhetoric of counter-corruption provided an enabling fiction for the neoliberalization of the Iraqi economy. Findings are discussed in detail.